Investigation of the influence of austenitization time on the structure and hardness of untempered ductile iron - Kakaš, Damir; Bajić, Vladimir; Škorić, Branko; Šiđanin, Leposava (Journal of Production Engineering, 1989)
Austempered ductile iron exhibits a favorable combination of ductility and abrasion resistance. It could potentially replace a range of construction steel with significant economic benefits. In this paper, we present the results of our investigation regarding the influence of austenitization time and austempering time. We have also developed a mathematical model to describe this influence.